A novel etching technique for surface treatment of zirconia ceramics to improve adhesion of resin-based luting cements - Eystein Ivar Ruyter; Nalini Vajeeston; Torbjørn Knarvang; Ketil Kvam (Acta Biomaterialia Odontologica Scandinavica)
Objectives: Bonding of zirconia crowns and bridges to abutments is important, not only bonding of the thin resin layer to the abutment, but also bonding to the zirconia ceramic is crucial. Both mechanical and chemical adhesion are desired. Mechanical retention of dental porcelain achieved by etching with moderately concentrated hydrofluoric acid is not possible with zirconia ceramics. The purpose of this study was to show that etching is possible with relative low melting fluoride compounds such as ammonium hydrogen difluoride and potassium hydrogen difluoride. Materials and methods: Before melting, the fluorides can be introduced as powders or as aqueous slurries to the contact surfaces of the zirconia. After melting, the yttria-stabilized zirconia surface revealed a surface similar to an HF-etched dental feldspathic porcelain surface. Shear bond testing (n = 10) was performed with zirconia attached to zirconia with the Duo-Link composite luting cement (Bisco) after treatment of the etched zirconia surfaces with Bis-Silane (Bisco) and the Porcelain Bonding Resin (Bisco). Results: Values for adhesive strength (mean ± standard deviation) after melt etching of the surfaces with initially dry powders were for K[FHF], (31.2 ± 7.5) MPa and for NH4[FHF] (31.0 ± 11.8) MPa. When initially aqueous slurries were applied, the values were for K[FHF] (42.7 ± 12.7) MPa and for NH4[FHF] (40.3 ± 10.0) MPa. Conclusion: Good adhesion to zirconia can be achieved by a procedure including etching with selected melted fluoride compounds.